The Influence of Financial Performance, Independent Commissioners, and Tax Avoidance on Company Value - Sidi Syahrozi, Teuku Muhammad; Nursita, Meta (Reformasi Administrasi, 2024)
This research aims to determine the influence of financial performance, independent commissioners and tax avoidance on company value. This research was conducted in the property and real estate sector listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The population in this study amounted to 92 companies. The sample was selected using a purposive sampling technique which selected companies using several criteria, so that the total sample obtained was 13 companies. The method used to analyze the influence of independent variables on the dependent in this research is panel data regression analysis using Eviews 9 software. The results of this research show that financial performance, independent commissioners, and tax avoidance together influence company value, financial performance has an significant influence to company value, independent commissioners do not have a significant effect on company value, tax avoidance does not have a significant effect on company value